Creative Work in Hadith Studies in Ceuta and Its Impact in the East - Klaina, Mekki (Taqaddumi: Journal of Quran and Hadith Studies, 2024)
This research examines creative work in Hadith studies in Ceuta due to its significance. Scholars in this region have been distinguished by their scholarly contributions, influencing others from different and being influenced by them as well. They introduced new areas in Hadith studies regarding book composition and refinement, similar to Al-Qadi 'Iyad in his book "Masyariq al-Anwar ala Sehah al-Athar," which had a clear impact on subsequent writings by scholars. This includes their discussions on "Tarajim al-Bukhari," as exemplified by Ibn Rushaid al-Sabti, whose influence extended to those who followed him and transmitted from him. They also played a prominent role in knowledge transmission in general, especially in Hadith, by categorizing books as indices, programs, proofs, dictionaries, and chains of narrators. These books among scholars contain the chains of transmission through which they reached the books of scholars, such as "Al-Ghunyah" by Al-Qadi 'Iyad, Ibn Khair al-Ishbili's Fihris, Al-Tujibi's Barnamaj, and others. They also took the lead in explaining Sahih Muslim and in preserving its narration in mosques and schools. All of this highlights that the Maghrebi and Andalusian scholarly figures went beyond mere knowledge transmission; they made valuable additions that contributed to the development of Islamic knowledge. Thus, the research objectives are to explore the contributions of Ceuta scholars in Hadith studies, evaluate their impact on others, and identify their distinctive aspects. In this study, we employed historical methodology, textual analysis, and comparative study techniques.